Information technology, development, and social change - Patel, Fay. (Routledge studies in development and society ;, 2012)
"The speed and cost effectiveness of new information technology has prompted many to view these innovations as a panacea for social and economic development. However, such a view flies in the face of continuing inequities in education, health, food, and infrastructure. This volume explores these issues - along with questions of access, privilege, literacy, training, and the environmental and health effects of information technologies in the developing world - arguing that a higher level of development does not always result from a higher level of technologization."--Provided by publisher.